2020
DOI: 10.1177/0300060520957547
|View full text |Cite
|
Sign up to set email alerts
|

Prediction model for anastomotic leakage after laparoscopic rectal cancer resection

Abstract: Objective This study was performed to identify risk factors for anastomotic leakage (AL) and combine these factors to create a prediction model for the risk of AL after laparoscopic rectal cancer resection. Methods This retrospective study involved 185 patients with rectal cancer who underwent laparoscopic resection from March 2012 to February 2017. Five risk factors were analyzed by multivariate analysis. A prediction model was established by combining the risk factors from the multivariate analysis, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Some studies have found that BMI is a risk factor, even an independent risk factor, for AL in resection for colorectal cancer [25][26][27]. However, the other studies also have shown that BMI is not related to the possibility of AL in rectal cancer surgery [28].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that BMI is a risk factor, even an independent risk factor, for AL in resection for colorectal cancer [25][26][27]. However, the other studies also have shown that BMI is not related to the possibility of AL in rectal cancer surgery [28].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with laparotomy, laparoscopic surgery shows promising efficacy and multiple benefits. 3 However anastomotic leakage (AL) has remains a devastating problem.…”
Section: Inductionmentioning
confidence: 99%
“…Laparoscopic surgery for rectal cancer is safe and feasible, 1,2 and it has become the preferred technique over open surgery. 3 An excellent surgical field is provided in a narrow pelvis by laparoscopic surgery during rectal resection.…”
Section: Introductionmentioning
confidence: 99%
“…Pelvic drainage serves as an indicator of anastomosis that reflects its integrity. 13 According to the experiences of different surgeons, clinical AL was indicated by the presence of clinical signs such as abnormal discharge from the pelvic drain tube (gas, pus, or feces), 3,4,14 peritonitis, 2,3,13 postoperative fever, 3,4 postoperative leukocytosis, 4 postoperative abdominal pain, 3 rectovaginal fistula, 4 or pelvic abscess. 4 If leakage is suspected, then abdominopelvic computed tomography (CT), 3,4,14 sigmoidoscopy, 4,14 rectal examination 4,14 or water-soluble contrast enema 4 should be conducted to confirm the diagnosis of AL.…”
Section: Introductionmentioning
confidence: 99%